2004
DOI: 10.1021/cm040057a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Epoxy-Functional Microspheres by Cationic Suspension Photopolymerization

Abstract: This article describes the development of a novel rapid one-step cationic suspension photopolymerization method for the synthesis of epoxy-functional polymeric microspheres ranging in size from 50 nm to 100 μm. Multifunctional silicon-containing epoxy monomers and oligomers were photopolymerized to produce microspheres in both in aqueous and nonaqueous suspensions using a variety of cationic photoinitiators. Various solvents with controlled polarities were employed to produce macroporous particles. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…10 The apparatus shown in Figure 1 consists of a cylindrical quartz reaction vessel (7.6 cm in diam by 12.7 cm) and an overhead stirrer (IKA, Inc. Wilmington, NC) equipped with a 5 cm diam three-paddle stainless-steel stirrer obtained from Fisher Scientific (Burr Ridge, IL) and a ultrasonication wand (13 cm) powered by a Vibra-Cell 750 W ultrasonicator (VCX 750, Vibracell Sonics, Newton, CT). The UV irradiation was supplied by a Hanovia 679A36 medium pressure mercury are lamp (Hanovia Ltd, Slough, UK) equipped with a 200 W power supply.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The apparatus shown in Figure 1 consists of a cylindrical quartz reaction vessel (7.6 cm in diam by 12.7 cm) and an overhead stirrer (IKA, Inc. Wilmington, NC) equipped with a 5 cm diam three-paddle stainless-steel stirrer obtained from Fisher Scientific (Burr Ridge, IL) and a ultrasonication wand (13 cm) powered by a Vibra-Cell 750 W ultrasonicator (VCX 750, Vibracell Sonics, Newton, CT). The UV irradiation was supplied by a Hanovia 679A36 medium pressure mercury are lamp (Hanovia Ltd, Slough, UK) equipped with a 200 W power supply.…”
Section: Apparatusmentioning
confidence: 99%
“…Recently, 10 we have reported that highly functional microspheres bearing epoxy groups can be obtained directly by the cationic suspension photopolymerization of multifunctional epoxy monomers. The general concept is depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…It can generally be carried out more rapidly and easily than the corresponding thermal processes, and several groups have obtained some good results. In these studies, dispersion, [2] aerosol, [23,24] cationic suspension, [25] and emulsion [26,27] photopolymerizations had been used to prepare PMMA, multiacrylate, and epoxy-functionalized microspheres, respectively. Either high-power UV lamps or complicated operations must be employed in these reports and none had dealed with preparations of copolymer microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…10 This synthetic method used a cationic photopolymerisation process, as well as conventional cationic vinyl and ring-opening polymerization, to realise a reaction that is well-known to be water sensitive. 11 Vinyl ethers are widely used in polymerisations for their ability to form networks with high efficiency for applications such as coatings, lithography etc. 9 Sangermano et.…”
mentioning
confidence: 99%
“…al. 11 report the synthesis of epoxy functionalized microspheres by cationic photopolymerization in aqueous conditions. It is important to underline that the typical water suspension polymerization comprises hydrophobic monomers, in which droplets (oil phase) are emulsified with surfactants in a continuous phase of water.…”
mentioning
confidence: 99%